Application of the AppSheet Application to Develop an InventorySystem for Goods at MSME Parabot Barokah - Barikly Mubarokan; Zulfa Hidni Nisa’i (Ebiz Prima Nusa, 2025)
This research aims to help MSME Parabot Barokah in overcoming the problem of inventory recording which is still done manually and is prone to errors. Using the AppSheet no-code platform connected to Google Sheets, researchers designed and implemented a digital inventory system that is simple, efficient, and easy to operate by non-technical users. The methods used include interviews, observations, and literature studies to understand the system needs and business processes of the store. The results of the implementation show that the application built is able to simplify the process of recording stock and sales, reduce the risk of data loss, and provide a visual display that facilitates analysis. The system is flexible, accessible online, and can be replicated by other MSMEs with similar conditions. This innovation proves that affordable and practical digital solutions can significantly improve the operational efficiency of small businesses.